Molecular docking study of anticancer activity of some s-triazine derivatives as HDAC6 inhibitors - Tuyền , Trương Ngọc; Em , Phạm Cảnh; Vi, Lê Thị Tường (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
A novel series of s-triazine derivatives was designed and screened for in silico anticancer activity in histone deacetylase 6 (HDAC6) target by molecular docking method using AutoDock Vina. Compound 12 showed the strongest interactions among all tested compounds with the affinity value of -11.3 Kcal/mol compared to the reference drugs Gedatolisib (-8.9 Kcal/mol) and Paclitaxel (-9.0 Kcal/mol) at the active site of HDAC6. In particular, compound 12 established strong hydrogen bonds and showed hydrophobic interactions that resemble Gedatolisib and Paclitaxel at amino acids such as SER150, LYS142, TRP261, and ALA145. Therefore, this compound could be a potential lead molecule and support for experimental testing against an HDAC6 enzyme as an anticancer agent.